Purification of Streptokinase and Human Plasmin and Their Interaction - Blatt, W. F; Segal, H; Gray, J. L (Thrombosis and Haemostasis, 1964)
Procedures have been described for the purification of streptokinase and human plasmin, and molecular weights of 42,600 and 88,800 respectively have been determined. Equilibration of streptokinase with plasmin solutions produced an inhibition of caseinolytic activity and indicated a mole-mole interaction. This inhibitory activity was lost following acid treatment. When these data are considered with the previously reported findings using plasminstreptokinase mixtures as plasminogen activators, it would appear that plasmin and streptokinase react to form a complex which has the ability to convert both human and bovine plasminogen to plasmin.